2003
DOI: 10.1046/j.1469-8137.2003.00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐root respiration in a loblolly pine and sweetgum forest growing in elevated CO2

Abstract: Summary• The loss of carbon below-ground through respiration of fine roots may be modified by global change. Here we tested the hypothesis that a reduction in N concentration of tree fine-roots grown in an elevated atmospheric CO 2 concentration would reduce maintenance respiration and that more energy would be used for root growth and N uptake. We partitioned total fine-root respiration ( R T ) between maintenance ( R M ), growth ( R G ), and N uptake respiration ( R N ) for loblolly pine ( Pinus taeda ) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
66
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 85 publications
9
66
2
1
Order By: Relevance
“…An increase in starch concentration is also likely to have contributed to greater sheath mass (Hendrix et al 1994;Seneweera et al 1994). It has been reported that, in species which have a limited potential to increase leaf area, the extra carbohydrate produced at elevated CO 2 is allocated to the stem or roots (George et al 2003). Our data suggest that in this rice cultivar, roots are the biggest carbon sinks with a large capacity to respond to elevated CO 2 .…”
Section: Resultssupporting
confidence: 49%
“…An increase in starch concentration is also likely to have contributed to greater sheath mass (Hendrix et al 1994;Seneweera et al 1994). It has been reported that, in species which have a limited potential to increase leaf area, the extra carbohydrate produced at elevated CO 2 is allocated to the stem or roots (George et al 2003). Our data suggest that in this rice cultivar, roots are the biggest carbon sinks with a large capacity to respond to elevated CO 2 .…”
Section: Resultssupporting
confidence: 49%
“…Although similar results have been observed in other ecosystems (George et al 2003, Tjoelker et al 1999, contrary results have also been reported (Janssens et al 1998, Edwards & Norby 1999, BassiriRad et al 1996, making broad statements on how elevated CO 2 affects root respiration difficult to infer. However, nitrogen contents of A. dumosa and L. tridentata roots sampled from the elevated CO 2 plots at the NDFF are not significantly different from those from ambient CO 2 plots (Nowak et al unpublished data), and L. tridentata root nitrogen was also not affected in our greenhouse experiment after 10 months of CO 2 treatment (Table 4).…”
Section: The Nevada Desert Face Facilitysupporting
confidence: 64%
“…These similar nitrogen contents may help explain the lack of differences in root respiration, which is highly correlated with nitrogen (2001, 2002, 2003, 2005, and 2006 (2001, 2002, 2003, 2005, and 2006). concentrations in root tissue across ecosystems . For loblolly pine and sweetgum, root nitrogen was not been altered with elevated CO 2 , nor was total root respiration (George et al 2003).…”
Section: The Nevada Desert Face Facilitymentioning
confidence: 88%
“…Root respiration provides the driving force for plant growth, biosynthesis, ATP production, cellular maintenance, and active transport in plant root (George et al 2003) and supports nutrient assimilation in roots (Amthor 1995). In addition, root respiration is estimated to account for approximately 50 % of soil respiration and plays a key role in forest ecosystem-level carbon (C) cycling (Bond-Lamberty et al 2004;Subke et al 2006).…”
Section: Introductionmentioning
confidence: 99%